Perbandingan Hasil Pemeriksaan Demam Tifoid Menggunakan Uji Widal pada Pasien Anak dan Dewasa di Puskesmas Polowijen - Liliosa Londong; Yeni Avidhatul Husna; Erni Yohani Mahtuti (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Typhoid fever is an infectious disease caused by Salmonella typhi bacteria and generally affects the digestive tract. This bacterium is commonly found in areas with poor sanitation, and diagnosis requires a combination of clinical and laboratory examinations. Typhoid fever is caused by Salmonella typhi, primarily attacking the digestive system and typically presenting with a fever lasting more than one week. This study applied a quantitative descriptive approach with a total sampling technique based on all medical record data of typhoid fever patients treated at Polowijen Public Health Center in 2024, totaling 150 respondents. The results showed that most patients were children and adolescents, with the highest prevalence in the 3–19 age group, consisting of 45 children (30%) and 53 adolescents–adults (35.33%). The disease tended to affect females more than males, partly due to women's frequent involvement in preparing and handling food and beverages. Patients commonly presented with positive Widal titers and clinical symptoms such as fever, headache, nausea, and vomiting. Data analysis utilized SPSS and cross-tabulation covering sex, age, duration of fever, and Widal titers. The findings indicated an association between age, clinical symptoms, and laboratory results with typhoid fever incidence. There was a correlation between high Widal titers and prolonged fever duration. Patients with titers ≥1/320 generally experienced fever lasting more than 6 days, particularly among adolescents–adults, whereas children tended to have lower titers (1/80–1/160) and a shorter duration of fever, although some cases with higher titers lasted up to 8 days.